Cardiac and vascular autonomic control in patients with hereditary angioedema - De Maria, Beatrice; Ranucci, Luca; Gino, Clara; Zulueta, Aida; Parati, Monica; Cesoni Marcelli, Azzurra; Zingale, Lorenza Chiara; Sideri, Riccardo; Dalla Vecchia, Laura Adelaide; Perego, Francesca (Frontiers in Physiology, 2025)
BackgroundRegulation of vascular permeability in hereditary angioedema due to C1 inhibitor deficiency (HAE-C1INH) is key to understanding the disease, but the role of the autonomic nervous system (ANS) in this mechanism remains unclear.PurposeThe aim of this study was to compare the cardiovascular autonomic response to the head-up tilt test (HUTT) in HAE-C1INH patients and matched healthy controls (HCs).MethodsHAE-C1INH patients were evaluated during a 1-week symptom-free period. Electrocardiogram (ECG) and beat-to-beat non-invasive arterial blood pressure (BP) were recorded in the supine position (REST) and during 70° tilt (TILT). Heart rate and systolic BP (SBP) variability indices were derived. Variance (σ2SBP) and low-frequency power (LFSBP) of SBP variability were used as markers of sympathetic vascular control.ResultsTwenty-five HAE-C1INH patients [13 male individuals, 44 (28.8–57.5) years] and 25 HCs [13 male individuals, 44 (30.8–54.3) years] were enrolled and divided into <45 and ≥45 age groups. Eighteen patients were on long-term prophylaxis (LTP). In the younger group, LFSBP increased from REST to TILT in both groups, with no differences. In older subjects, HAE-C1INH patients showed higher σ2SBP [21.2 (9.3–59.2) vs. 7.5 (1.9–14.6) mmHg2] and a greater LFSBP increase [9.4 (4.6–22.4) vs. 0.9 (0.2–7.6) mmHg2] than HCs during TILT, suggesting sympathetic hyperactivation. No significant group differences in cardiac autonomic control were observed during REST or TILT, regardless of age. Findings in the LTP subgroup mirrored those of the full cohort.ConclusionOlder HAE-C1INH patients display altered vascular autonomic regulation, with an exaggerated sympathetic response during orthostatic stress. Further studies are needed to assess the role of LTP in these alterations.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06408805?cond=Hereditary%20Angioedema&term=autonomic&rank=1